Modelling Innovation Activity in Regional Innovation Networks Using Fuzzy Cognitive Maps - Hájek, Petr; Stejskal, Jan; Procházka, Ondřej (Academic Conferences and Publishing International, 2016)
Intensive communication and collaboration between actors are critical for a successful innovation process. This knowledge exchange can be effectively facilitated by geographical proximity inside regional innovation networks. Previous literature has shown that regional innovation networks are complex and dynamic systems, which cannot be effectively modeled using traditional methods such as structural equation models or system dynamics simulation. The main issue to be addressed is the uncertainty in knowledge linkages. Here, we use the amount of financial support for cooperative projects in applied research and experimental development as listed by the Technology Agency of the Czech Republic (TACR) as a proxy for these linkages. To model the dynamics and uncertainty in regional innovation networks, we have developed a fuzzy cognitive map that allows for effective simulation of knowledge linkages when given the initial settings. In this way, we demonstrate the short- and long-term effects of financial support on the innovative activity of individual organizations (measured by patent applications). Using the data for one Czech region collected from the TACR database for 2011–2015, we demonstrate the evolving patterns of various scenarios of innovation policy and financial support, respectively. These simulations indicate the strong central position of universities in regional innovation networks.
Modelování inovační aktivity v regionálních inovačních sítích pomocí fuzzy kognitivních map
Keywords: regional innovation network; R&D cooperation; financial support; simulation; fuzzy cognitive map; regionální inovační sítě; spolupráce v oblasti výzkumu a vývoje; finanční podpora; simulace; fuzzy kognitivní mapa